Cultural Communication and Artistic Expression of the Mambilla People of Taraba State in the Digital Era: A Histo-Cultural Investigation - Ngantem, Linus Mun; Tengya, Pomak; Jibaniya, Achonma Jonah (Darul Yasin Al Sys, 2025)
This study investigates the impact of digital media on the cultural communication and artistic expression of the Mambilla people of Taraba State in the digital era, focusing on how digital technologies have transformed traditional practices and communication methods. Guided by Cultural Studies Theory and Digital Cultural Studies Theory, the research explores the influence of digital media on Mambilla cultural communication, the transformation of artistic expressions, and the tension between cultural preservation and authenticity loss. A mixed-methods approach was employed, combining qualitative in-depth interviews with quantitative surveys to gather insights from the Mambilla community. Findings reveal that digital media, particularly social media platforms, have expanded the global reach of Mambilla cultural practices while simultaneously raising concerns over the distortion of traditional art forms and erosion of authenticity. The study concludes that digital technologies present both opportunities and risks: they enable preservation and wider dissemination of culture, yet challenge the maintenance of cultural integrity. Recommendations include implementing digital literacy programmes for older generations, establishing a digital cultural archive for Mambilla heritage, and formulating cultural guidelines for content creators to safeguard authenticity in the digital space.